Rectosigmoid sparing en bloc pelvic resection for fixed ovarian tumors: Surgical technique and perioperative and oncologic outcomes - Shan, Ying; Jin, Ying; Li, Yan; Gu, Yu; Wang, Wei; Pan, Lingya (Frontiers in Oncology, 2022)
Purpose Patients with advanced ovarian cancer often undergo en bloc rectosigmoid resection with total hysterectomy to completely debulk the pelvis. We describe a unique rectosigmoid sparing en bloc pelvic resection technique for fixed ovarian tumors infiltrating the colon wall. Methods From July 2020 to June 2021, 20 patients with advanced epithelial ovarian cancer (EOC) underwent rectosigmoid sparing en bloc pelvic resection successfully at our institution. We summarized our surgical technique and the peri-operative and oncological outcomes. Results Twenty cases with bowel infiltration achieved en bloc pelvic resection with rectosigmoid tumorectomy in a centripetal fashion. Only two patients required mucosal repair. None of the patients experienced any complications associated with en bloc resection. No pelvic recurrence occurred within the median follow-up time of 12 months. Conclusion Rectosigmoid sparing en bloc pelvic resection may be feasible for select patients with fixed ovarian tumors infiltrating the colon wall.